Differences among protected area governance types matter for conserving vegetation communities at risk of loss and fragmentation. (July 2020) - Archibald, Carla L.; Barnes, Megan D.; Tulloch, Ayesha I.T.; Fitzsimons, James A.; Morrison, Tiffany H.; Mills, Morena; Rhodes, Jonathan R.
Abstract: Private and Indigenous protected areas are a growing component of the global protected area network. Countries can benefit from a diversity of protected area governance types as a means of creating complementarity and robust national reserve networks. However, strategically allocating resources among governance types requires a greater understanding of similarities and differences in how each protected area governance type represents ecosystems. Using a novel approach based on compositional analysis, we investigate to what extent government, private and Indigenous protected areas represent at-risk vegetation communities that have historically been impacted by habitat loss and fragmentation. We show that the relative representation of at-risk vegetation is different between government, private and Indigenous protected areas. Government and privately protected areas have a higher relative representation of at-risk vegetation over lower concern vegetation, a pattern which was not found for Indigenous protected areas. These results reflect how land tenure, and subsequently protected areas, have historically been allocated in Australia. We urge researchers and policymakers to recognize how the opportunities and constraints associated with government, private and Indigenous protected areas may affect their contribution towards conservation goals. Insights from such studies are important to develop complementary and robust conservation strategies across protected area governance types. Highlights: Private and Indigenous protected areas are a growing component of the global protected area network Compositional analysis can be used to assess ecological representation when conservation actions are constrained by land tenure Government, Indigenous and private protected areas contributed in different ways to at-risk vegetation protection in Australia Government, Indigenous and private protected area establishment can be shaped by their governance context and the historical land use legacy Insights from this study are can inform complementary and robust conservation strategies across protected area governance types.